THE INFLUENCE OF ORGANIZATIONAL INNOVATION AND DIGITAL TRANSFORMATION ON FIRM PERFORMANCE OF FINANCIAL TECHNOLOGY (FINTECH) COMPANIES IN INDONESIA - Wafa Zakkiyah, Wafa (President University, 2024)
The current industrial environment is changing rapidly, including in Indonesia.When the industrial environment changes rapidly and market competition becomes verytight, dynamic capability is needed to adapt to environmental changes (Teece, Pisano, &Shuen, 1997). When changes in the industrial environment occur, market uncertainty willincrease significantly, and thus, organizational innovation will be influenced by dynamiccapability (Pai & Chang, 2013). Innovation is considered a source of competitiveadvantage for companies that can improve firm performance (Ahuja & Katila, 2001).Firm performance is not only influenced by organizational innovation, but is alsoinfluenced by digital transformation. Fintech has existed in Indonesia for decades, but,in recent years, the fintech industry has succeeded in revolutionizing the way peopleinteract with financial services (AFPI, 2023). Therefore, this research will discuss theinfluence of organizational innovation and digital transformation on the firmperformance of financial technology (fintech) companies in Indonesia.Keywords: dynamic capability, organizational innovation, digital transformation, financial technology